THE IMPACT OF AUDIT COMMITTEE CHARACTERISTICS ON THE SHARE HOLDER VALUE CREATION: EVIDENCE FROM INDONESIA - Maghriby, Bimbim; Ramdani, Dani; Muslim, Ade Imam (Jurnal Riset Keuangan dan Akuntansi, 2024)
This research seeks to investigate the characteristics of company performance audit committees and their impact on company value. We conducted an analysis of family companies in Indonesia, especially family companies that are over 20 years old. We analyzed the data we collected using multiple regression. The research results provide quite strong empirical evidence that the frequency of audit committee meetings and the company's financial performance have positive significance in increasing shareholder value. This research provides implications for family companies, especially for maintaining good financial performance and maintaining the independence of the audit committee through the involvement of external audit committee members. It is hoped that the selected audit committee will not come from the family or have any family affiliation with the companyKeywords: audit committee characteristics, financial performance, shareholder value.